What's cooking, Mom?: narratives about food and family - Cassidy, Tanya; Pasche Guignard, Florence (Demeter Press, 2015)
Intro -- What's Cooking, Mom? Narratives about Food and Family -- Copyright Notice -- Title Page -- Table of Contents -- Acknowledgements -- Introduction TANYA M. CASSIDY AND FLORENCE PASCHE GUIGNARD -- I. Positionality, Ethics, and Reflexivity -- 1. Talking Back (to Myself)CHRISTIN L. SEHER -- 2. It's a Gluten World Out There: A Celiac Mother's Socialization Story JOYCE L. MANDELL -- 3. Revisiting and Reconstructing Maternal Sustenance: An Autoethnographic Account of Academic Motherhood SARAH N. GATSON -- 4.Meeting Myself for Dinner: Negotiating the Multiplicity of Positionality While Feeding the Family LORIN BASDEN ARNOLD -- 5.Production, Process, and Parenting: Meanings of Human Milk Donation TANYA M. CASSIDY AND CONRAD BRUNSTRÖM -- II. Memories, Responsibility, and Authority -- 6. Feeding Hannah ROBIN SILBERGLEID -- 7.Farm Culture, the Politics of Food, and Maternal Guilt B. LEE MURRAY -- 8.When Feeding Your Family Is a Full-time Job KARI O'DRISCOLL -- 9.My Mother Did Not Cook DOMINIQUE O'NEILL -- 10.Fortress of Confection: Lessons from My Yankee Grandmother ERICA CAVANAGH -- 11.Dreams of Exclusive Breastfeeding: Mothering Without Enough Milk GRACE M. CHO -- III. Negotiating Intercultural Maternal Experiences -- 12.Lebkuchen Lesson: Teaching Our Children Through Traditional Foods EMILY WEISKOPF-BALL -- 13.Scary Candy, Goldfish Crackers, and Kale Chips: Feeding and Parenting Our New Canadian Daughter in Toronto FLORENCE PASCHE GUIGNARD AND THOMAS GUIGNARD -- 14.Wa and Wa-shoku: Mothering and Food as an American in Japan WENDY JONES NAKANISHI -- 15.The Rebellious Bento Box: Slapdash Western Mothering in Perfectionist Japan MEREDITH STEPHENS -- 16.An Ethnographic Analysis of U.S. Culture and Carribean Food Practices ROSA E. SOTO AND SHARMILA PIXY FERRIS.